2021
DOI: 10.1186/s43088-021-00102-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutational hotspots and conserved domains of SARS-CoV-2 genome in African population

Abstract: Background Since outbreak in December 2019, the highly infectious and pathogenic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused over a million deaths globally. With increasing burden, the novel coronavirus has posed a dire threat to public health, social interaction, and global economy. Mutations in the SARS-CoV-2 genome are moderately evolving which might have contributed to its genome variability, transmission, replication efficiency, and virulence in different region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…Similarly, one study (Omotoso et al 2021 ) previously described a non-synonymous mutation at position 28854C > T (S194L), and in the current study such a mutation was observed in the N protein, which altered the original sequence of the open reading frame for the nucleocapsid (N) protein which is recognized to be important in virion assembly and structure (Weber et al 2021 ). Apart from frequent mutations, four variants were found in the spike glycoprotein (S); while triple mutations observed (L452R, E583D, D614G) were non-synonymous and were reported previously in strains from other countries (Harvey et al 2021 ) (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Similarly, one study (Omotoso et al 2021 ) previously described a non-synonymous mutation at position 28854C > T (S194L), and in the current study such a mutation was observed in the N protein, which altered the original sequence of the open reading frame for the nucleocapsid (N) protein which is recognized to be important in virion assembly and structure (Weber et al 2021 ). Apart from frequent mutations, four variants were found in the spike glycoprotein (S); while triple mutations observed (L452R, E583D, D614G) were non-synonymous and were reported previously in strains from other countries (Harvey et al 2021 ) (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Previous studies have shown that remdesivir abrogates the canonical replicase activity of RdRp [ 50 , 51 ]. Notably, both palm and NiRAN domains amino acid sequences are highly conserved among various variants of concerns identified for SARS-CoV-2 [ 52 , 53 ]. We hypothesized that a combinatorial therapy of remdesivir and sorafenib may show synergistic effect to abolish the dual enzymatic activities of RdRp.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another study has shown the role of NiRAN domain in formation of a cap core structure [ 71 ]. In addition, the NiRAN domains of the RdRp molecules from the various variants of SARS-CoV-2, including the variants of concern, exhibit high degree of conservation, especially in the putative active site residues such as K73 and D218 [ 52 , 53 ]. Together our report and these recent studies hint at the indispensible nature of RdRp NiRAN domain for a successful viral replication in Nidoviruses, thus it is pertinent to explore in vivo anti-viral efficacies of compounds targeting the NiRAN catalytic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore coronaviruses in general, the quasispecies evolutionary processes have been well described (39,(42)(43)(44)(45)(46)(47)(48)(49). To support this, the ongoing SARS-CoV-2 outbreak in humans displayed widespread mutation/deletions and evolution in the critical genes of ORF1a (46,(50)(51)(52)(53)(54); spike gene (46,50,51,55,56); ORF3 (50,(57)(58)(59); and ORF8 (33,50,(60)(61)(62)(63)(64)(65) those viral proteins regulates the virus transmission, better adaptability to host and evasion of the host immunity. Furthermore, the presence of selection pressure for the evolution of the SARS-CoV-2 has been highly characterized (10,52,66,67).…”
Section: Discussionmentioning
confidence: 98%